Notes on archaeological experience: expedition in San José Bocay, Jinotega, phase II (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
The Ulúa-Matagalpa Cultural Science Foundation aims to contribute to the knowledge of prehistory, history, anthropology and linguistics of the territory of north-central Nicaragua, southern Honduras and eastern Salvador. To do this, it seeks to integrate and compare archaeological and anthropological elements that allow associations to be made in the territory proposed as the Ulúa Matagalpa cultural area. The present study was conducted in the municipality of San José Bocay, department of Jinotega, in the districts of Santa Rosa de Tapaskún and Runflin, extreme northwest of the sector of Ayapal. The investigation counted with the financing of the Embassy of the Grand Duchy of Luxembourg and with the immense contribution of the Matagalpa Indigenous People quinees provided us with their facilities to carry out the work of the Laboratory and systematize the results of the Bocay expedition 2016-17. During the field investigation, there was a team of seven researchers from the Foundation, including Dr. Rigoberto Navarro, Msc. Mario Rizo, Lic. Frania Blandón, Lic. Tania Blanco, Eng. Arturo López and Lic. Cristopher Gago. Also, participation during the work in situ two students of Unan Managua and three colleagues of the Association Sigos del Rio de Wiwili. Separately, the laboratory analysis of the ceramics and lithics recovered through the excavation was carried out, in this process the Msc participated. Deyvis Oporta and Lic. Roberto Sirias with whom we worked in a Type-Variety analysis study to start building a chronology of the Segovias.
Keywords: Prehistory of Bocay, county of Runflin and Santa Rosa de Tapaskun.